Gestão democrática escolar : a participação como princípio pedagógico - Brustolin, Maite Anziliero (2011)
The present research has as objective to analize the requirements needed to be made effective democratic management in the educational process of school with the intention of making an educational principle to participate. The research assumes that the practice of democratic governance is a link for all teachers in action in schools and public school systems regarding the articipation processes. To realize this purpose, the research is justified by the need to investigate and reflect how happens Democratic Management School, its concepts, dilemmas and challenges in everyday school life and make it a political, educational and democratic. Initially covers the key concepts that underlie the process of Democratic Management, and then analyzes the Democratic Administration in the context of the laws (Constitution of 1988, LDB 9394/96 and PCNs) and finally describes the possibilities of realization of the Democratic Management educational process of the school taking the pedagogical Political Project as the main vector for its implementation